Nationalism, terrorism, communalism : essays in modern Indian history - Heehs, Peter (Delhi ; New York : Oxford University Press, 1998)
With special reference to Bengal; articles.
Includes bibliographical references and index.
Keywords: Nationalism -- India -- Bengal; Terrorism -- India -- Bengal; Communalism -- India -- Bengal; Bengal (India) -- Politics and government -- 20th century